Advanced taxation - Association of Chartered Certified Accountants (Great Britain) (London : Financial Training Courses Ltd., 1988)
This study pack was prepared for students taking the ACCA level 3 examination, taxation and tax management in 1989.
Level 3, paper 3.3. Volume 2.
asm 22/01/2019
Loans
Keywords: Tax; Taxation; Tax management